Spatial Distribution of Noise Released from Iron and Steel Industry and their Effects on Human Health in the Lahore City, Pakistan - Anum Liaqut; Isma Younes; Rakhshanda Sadaf (Journal of Basic & Applied Sciences, 2017)
This research investigates the phenomenon of perception of people about industrial noise pollution and its effects on human health. Thirty-six (36) industries were selected for estimation of noise levels and its effects on human health. Concurrently, samples of one hundred and fifty (150) respondents were also taken from nearby residential area, using random sampling method. The key tool of data collection was well-structured questionnaires consisting of twenty-one questions. Chi-Square test was used for examination of data, which illustrated effects of industrial noise on people living in industrial zone. The noise level results indicated that the mean values were exceeding permissible environmental standard used in Pakistan. Majority of respondents (50.6 %) were conscious about the basic reason of noise pollution in study area. Eighty-two percent (82%) people have opinion that old technology was the basic cause for noise pollution. It was shocking to see the results which indicate that 99.8% people are suffering from noise related diseases. This include 81.3% with increase anger, 81.5% with ear ache, 16% with ear discharge, 79.3% with high blood pressure, 78% with depression, 77.3% temporary hearing loss, 9.3% permanent hearing loss. Only 23.3% of people conduct regular hearing test.